Pathogenic in-Frame Variants in SCN8A: Expanding the Genetic Landscape of SCN8A-Associated Disease - Wong, Jennifer C.; Butler, Kameryn M.; Shapiro, Lindsey; Thelin, Jacquelyn T.; Mattison, Kari A.; Garber, Kathryn B.; Goldenberg, Paula C.; Kubendran, Shobana; Schaefer, G. Bradley; Escayg, Andrew (Frontiers in Pharmacology, 2021)
Numerous SCN8A mutations have been identified, of which, the majority are de novo missense variants. Most mutations result in epileptic encephalopathy; however, some are associated with less severe phenotypes. Mouse models generated by knock-in of human missense SCN8A mutations exhibit seizures and a range of behavioral abnormalities. To date, there are only a few Scn8a mouse models with in-frame deletions or insertions, and notably, none of these mouse lines exhibit increased seizure susceptibility. In the current study, we report the generation and characterization of two Scn8a mouse models (ΔIRL/+ and ΔVIR/+) carrying overlapping in-frame deletions within the voltage sensor of domain 4 (DIVS4). Both mouse lines show increased seizure susceptibility and infrequent spontaneous seizures. We also describe two unrelated patients with the same in-frame SCN8A deletion in the DIV S5-S6 pore region, highlighting the clinical relevance of this class of mutations.